IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI BERBASIS PENDEKATAN HUMANISTIK DALAM KAITAN PENINGKATAN MINAT DAN HASIL BELAJAR KOGNITIF DI KELAS II SDN 038 TENGGARONG - Sigit Purwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Implementation of Differentiated Learning Based on a Humanistic Approach in Grade II at SDN 038 Still Faces Challenges. Therefore, the purpose of this study is to examine the implementation of differentiated learning using a humanistic approach employed by teachers in relation to increasing students’ learning interest and cognitive learning outcomes in Grade II at SD Negeri 038 Tenggarong.The research method used is qualitative research, with respondents including teachers, students, and the principal. Respondents were selected through purposive sampling, based on the research objectives. Snowball sampling was also applied by involving participants identified through the main respondents. The research procedure began with the researcher preparing instruments and differentiated learning tools using a humanistic learning theory approach. The research was conducted through interviews and observations. Data were analyzed through preliminary conclusions and final conclusions drawn during the interview process. The results of the study showed that the teacher respondent had planned, implemented, and evaluated the implementation of differentiated learning based on a humanistic approach in Grade II at SDN 038 Tenggarong. The student respondents had prepared for, engaged in, and achieved improved learning outcomes in the form of increased learning interest and cognitive performance. The principal respondent had facilitated the planning, implementation, and evaluation processes of differentiated learning using a humanistic approach, thereby contributing to improved student motivation and cognitive achievement.